Study on propagation properties of UWB signal waveform - LIU Yuan-jian; ZHANG Ye-rong (Tongxin xuebao)
Investigating the propagation properties of Ultra-wideband （UWB） were the essential topics in UWB channel theory.Based on Fourier transformation,Various UWB pulse waveform with indoor reflection,refraction and diffraction is studied.Moreover,a novel approximate formula of n order modified Bessel function was put forward.Finally,a comparison of Fourier transformation results with time-domain accurate results shows good agreements.